2021
DOI: 10.5194/esurf-9-1347-2021
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid data–model approach to map soil thickness in mountain hillslopes

Abstract: Abstract. Soil thickness plays a central role in the interactions between vegetation, soils, and topography, where it controls the retention and release of water, carbon, nitrogen, and metals. However, mapping soil thickness, here defined as the mobile regolith layer, at high spatial resolution remains challenging. Here, we develop a hybrid model that combines a process-based model and empirical relationships to estimate the spatial heterogeneity of soil thickness with fine spatial resolution (0.5 m). We apply… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(114 reference statements)
1
4
0
Order By: Relevance
“…Note that the blended area in the top panel indicates the area that is not shown by the geological cross section. is in agreement with other studies that showed that steeper slopes are usually related to higher runoff and less groundwater infiltration [e.g., (23)], while increased soil erosion leads to a thinner soil cover (80), which also likely contributes to a higher aggregated resistivity response.…”
Section: Discussionsupporting
confidence: 92%
“…Note that the blended area in the top panel indicates the area that is not shown by the geological cross section. is in agreement with other studies that showed that steeper slopes are usually related to higher runoff and less groundwater infiltration [e.g., (23)], while increased soil erosion leads to a thinner soil cover (80), which also likely contributes to a higher aggregated resistivity response.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is a difference in two grassland-dominated zones, Zone 5 and Zone 1, with the high-elevation grassland less sensitive to droughts, possibly owing to increased water availability at higher elevation. In addition, in a separate study by Yan et al (2021), the soil thickness and associated parameters such as soil diffusion coefficients are found to be distinctly different between the two zones in this domain (Zone 1 and Zone 2).…”
Section: Discussionmentioning
confidence: 72%
“…This hierarchical representation provides a tractable framework for watershed characterization. Furthermore, Yan et al (2021) developed two separate parameterizations for the soil evolution model in the two hillslopes that belonged to Zones 1 and 2 and then simulated the variable soil thickness within those hillslopes. In this way, our method can improve model parameterization in large-scale hydrological models by honoring distinct boundaries and water/element export contributions and provide a new comprehensive way of linking above-and below-ground properties to watershed functions critical to maintaining water resources.…”
Section: Discussionmentioning
confidence: 99%
“…Research has made much progress in addressing these knowledge gaps. For example, many physically based and empirical soil-depth models are available (Roering, 2008;Pelletier and Rasmussen, 2009;Ho et al, 2012;Catani et al, 2010;Nicótina et al, 2011;Gomes et al, 2016;Patton et al, 2018;Yan et al, 2021;Xiao et al, 2023), making it possible to estimate the field distribution of soil depth in landslide prone areas (Godt et al, 2008a;Segoni et al, 2009;Ho et al, 2012). Some studies have combined field or laboratory measured properties with mapped lithologic characteristics and statis-R. L. Baum et al: Assessing locations susceptible to shallow landslide initiation tical analysis to describe the spatial distribution of soil properties (Godt et al, 2008b;Tofani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%